2003
DOI: 10.1007/s00438-003-0929-9
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of rice tissues by two-dimensional electrophoresis: an approach to the investigation of gibberellin regulated proteins

Abstract: Protein databases constructed using high-resolution two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) were used to explore the proteome expressed in various rice tissues. Proteins from leaf sheath, root, and cultured suspension cells were systematically analyzed using 2D-PAGE, mass spectrometry and Edman sequencing, followed by database searching. In all, 79 of the 431 spots detected by 2D-PAGE in the leaf sheath, 73 of the 508 spots in the root and 140 of the 962 spots in the cultured suspension ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 57 publications
3
62
1
1
Order By: Relevance
“…The second largest group consists of proteins involved in metabolism. This is in contrast to the total rice proteome, in which metabolic proteins form the largest percentage of proteins in leaf sheath [42], but in the phosphoproteome analysis, they formed the second largest percentage. Other identified phosphoproteins are involved in energy production and transcription, and the functions of 7 proteins are unknown.…”
Section: Detection Of Phosphoproteins In Rice Leaf Sheath By In Vitrocontrasting
confidence: 57%
See 3 more Smart Citations
“…The second largest group consists of proteins involved in metabolism. This is in contrast to the total rice proteome, in which metabolic proteins form the largest percentage of proteins in leaf sheath [42], but in the phosphoproteome analysis, they formed the second largest percentage. Other identified phosphoproteins are involved in energy production and transcription, and the functions of 7 proteins are unknown.…”
Section: Detection Of Phosphoproteins In Rice Leaf Sheath By In Vitrocontrasting
confidence: 57%
“…Of these proteins, 2-D LC identified 9 that were up-regulated and 9 that were down-regulated by GA 3 treatment, while 2-D DIGE identified 4 up-regulated and 4 down-regulated proteins. In our previous studies we showed that 32 proteins from leaf sheaths grown in vitro [41] and 8 proteins from leaf sheaths in intact rice plants [42] were regulated by GA during elongation. Most of the 32 proteins detected using leaf sheath segments were stress-related proteins.…”
Section: Differential Proteomics Using 2-d Lc and 2-d Digementioning
confidence: 95%
See 2 more Smart Citations
“…Several studies have dealt with the construction of proteomes for complex samples from rice, such as leaf, embryo, endosperm, root, stem, shoot, anther, and callus (11)(12)(13)(14)(15)(16)(17)(18)(19), and subcellular components such as Golgi bodies, mitochondria, plasma membrane, vacuolar membrane, Golgi membrane, and chloroplasts have also been studied (20 -22). These reports have focused on mapping the proteins and constructing a data base of expressed proteins of various tissues and subcellular components but have not addressed the changes in protein expression over time that are critical to understanding development in complex organisms.…”
mentioning
confidence: 99%